Shadowing the Anthropocene: Eco-Realism for Turbulent Times. - Ivakhiv, Adrian (Punctum Books, 2018)
A spectre is haunting humanity: the spectre of a reality that will outwit and, in the end, bury us. "The Anthropocene," or The Human Era, is an attempt to name our geological fate - that we will one day disappear into the layer-cake of Earth's geology - while highlighting humanity in the starring role of today's Earthly drama. In Shadowing the Anthropocene, Adrian Ivakhiv proposes an ecological realism that takes as its starting point humanity's eventual demise. The only question for a realist today, he suggests, is what to do now and what quality of compost to leave behind with our burial. The book engages with the challenges of the Anthropocene and with a series of philosophical efforts to address them, including those of Slavoj Žižek and Charles Taylor, Graham Harman and Timothy Morton, Isabelle Stengers and Bruno Latour, and William Connolly and Jane Bennett. Along the way, there are volcanic eruptions and revolutions, ant cities and dog parks, data clouds and space junk, pagan gods and sacrificial altars, dark flow, souls (of things), and jazz. Ivakhiv draws from centuries old process-relational thinking that hearkens back to Daoist and Buddhist sages, but gains incisive re-invigoration in the philosophies of Charles Sanders Peirce and Alfred North Whitehead. He translates those insights into practices of "engaged Anthropocenic bodymindfulness"--Aesthetic, ethical, and ecological practices for living in the shadow of the Anthropocene